Analisis Flash Sale Berdasarkan Undang-Undang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat - Oky Tiara Putri; Arief Suryono (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Today's electronic transactions are facilitated by the many Marketplaces and Online Shops that sellers and buyers can visit. Various platforms implement Flash Sales at certain moments as a form of promotion. In this case, forms of Predatory Pricing are found which include Unfair Business Competition in Predatory Pricing. The following research aims to examine and explain the Flash Sale method in Online Shops and its indications of unhealthy business competition. The following research was carried out using descriptive qualitative methods using a normative juridical approach by analyzing phenomena that exist in real conditions with statutory regulations simultaneously. Based on the analysis results, it is known that not all Flash Sale Programs provide prices far below production. However, the implementation of flash sales which drastically reduce prices is a clear indication of unhealthy business competition. Considering the drop in prices posted on the Flash Sale can reach 80% of the original market price. Based on the results of analysis using the Price-Cost Test, massive discounts by E-Commerce are a form of Predatory Pricing.